Growth of a TiNb adhesion interlayer for bioactive coatings - Tolde, Zdeněk; Starý, Vladimír; Cvrček, Ladislav; Vandrovcová, Marta; Remsa, Jan; Daniš, Stanislav; Krčil, Jan; Bačáková, Lucie; Špatenka, Petr (Materials science & engineering. C, Materials for biological applications, 2017)
Surface bioactivity has been under intensive study with reference to its use in medical implants. Our study is focused on coatings prepared from an electroactive material which can support bone cell adhesion. Until now, hydroxyapatite films have usually been utilized as a chemically-active surface agent. However, electrically-active films could set a new direction in hard tissue replacement. As a base for these films, it is necessary to prepare an intermediate film, which can serve as a suitable barrier against the possible diffusion of some allergens and toxic elements from the substrate. The intermediate film also improves the adaptation of the mechanical properties of the basic material to an electroactive film. The aim of our work was to select an implantable and biocompatible material for this intermediate film that is suitable for coating several widely-used materials, to check the possibility of preparing an electroactive film for use on a material of this type, and to characterize the structure and several mechanical properties of this intermediate film. TiNb was selected as the material for the intermediate film, because of its excellent chemical and mechanical properties. TiNb coatings were deposited by magnetron sputtering on various substrates, namely Ti, Ti6Al4V, stainless steel, and bulk TiNb (as standard), and important properties of the layers, e.g. surface morphology and surface roughness, crystalline structure, etc., were characterized by several methods (SEM, EBSD, X-ray diffraction, nanoindentation and roughness measurement). It was found that the structure and the mechanical properties of the TiNb layer depended significantly on the type of substrate. TiNb was then used as a substrate for depositing a ferroelectrically active material, e.g., BaTiO3, and the adhesion, viability and proliferation of human osteoblast-like Saos-2 cells on this system were studied. We found that the electroactive BaTiO3 film was not only non-cytotoxic (i.e. it did not affect the cell viability). It also enhanced the growth of Saos-2 cells in comparison with pure TiNb and with standard tissue culture polystyrene wells, and also in comparison with BaTiO3 films deposited on Ti, i.e. a material clinically used for implantation into the bone.
Keywords: Prostheses and Implants; osteoblasty; povrchové vlastnosti; lidé; Titanium; adheziva; Adhesives; titan; slitiny; Durapatite; Materials Testing; X-Ray Diffraction; difrakce rentgenového záření; Osteoblasts; Alloys; testování materiálů; protézy a implantáty; Surface Properties; hydroxyapatit; Humans